Capital, empowerment and hope in reducing risks for recidivism amongst women offenders in Sungai Udang Prison, Malaysia - Sheikh Zainal, Siti Muhaza (2015)
Recidivism amongst women offenders in Malaysia is slowly increasing each year. This marked a need to grow concerned about the profound impact the problem has on the women themselves, family, and their children and even to the community at large. This problem occurs because traditionally efforts to reduce recidivism derived mainly from using the problems and needs approach in the women offender rehabilitation programs. The top-bottom method was also very much used in constructing the type of rehabilitation for women offenders’ community in the prison. The objective of this study is to discover the strengths of women offenders’ community typically in Sungai Udang Prison in order to ascertain the capabilities they possess in determining their own goal to reduce their risks for recidivism. This research uses mixed method approach where quantitative findings are connected into the analysis of qualitative studies. Research instruments used were sets of questionnaires including a translated version of the Roberts Empowerment Scale and the Herth Hope Index. A total of 40 respondents of Sungai Udang Prison is selected through using non-probable purposive and maximum variation sampling technique. The respondents are Malaysians with varied ages, race or ethnics and types of offenses. Out of 34 respondents who are involved in the qualitative round, in depth interview is performed to 13 randomly selected respondents. This study also employs data triangulation that involves 8 community leaders. Quantitative results showed that besides having social capital and human capital during stay in prison, women offenders’ community also possess a high level of empowerment and hope in life. These are the capitals that motivate women offenders’ community to achieve risks for recidivism. Using Mayring’s Content Analysis, psychological empowerments emerge as another important capital the women offenders’ community own. By means of empowerment process that utilizes all the strengths discovered, women offenders’ community is found to be able to plan perceptively about the strategies they will use to reduce their risks for recidivism during post release. These strategies or empowerment goals are the “Fast Track to Target”, “Listen and I Will Be Listened To”, “Trading Shame for Guts”, “Give and I Will Get Back”, “If I Cannot Join, I’ll Leave Them” and “Please Help Me I’m Falling”. Discussions about the link between capitals, empowerment and hope in the context of psychological empowerment were also set forth.